Pengaruh Attitude, Subjective Norm, Perceived Behavioral Control, dan Religiusitas Terhadap Niat Berwakaf Uang Pada Mahasiswa Ekonomi Islam di Surabaya - Della Dwi Ramadhani; Ramdani Ramdani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of attitude, subjective norm, perceived behavioral control, and religiosity on the intention to donate cash waqf among Islamic economics students in Surabaya. This study employed a quantitative research method. Data were collected via an online questionnaire using Google Forms and a Likert scale. The sampling technique used was purposive sampling. The sample consisted of 162 respondents. Data analysis was conducted using PLS-SEM with SmartPLS 4.0 to examine the influence of attitude, subjective norm, perceived behavioral control, and religiosity on the intention to donate cash waqf among Islamic economics students in Surabaya. The results of this study indicate that attitude, subjective norm, and perceived behavioral control have a significant effect on the intention to donate cash waqf among Islamic economics students in Surabaya. Meanwhile, religiosity does not have a significant effect on the intention to donate cash waqf among Islamic economics students in Surabaya.